2009
DOI: 10.1002/ajim.20703
|View full text |Cite
|
Sign up to set email alerts
|

Variation across the agricultural season in organophosphorus pesticide urinary metabolite levels for Latino farmworkers in eastern North Carolina: Project design and descriptive results

Abstract: Background-Community Participatory Approach to Measuring Farmworker Pesticide Exposure, PACE3, used a longitudinal design to document pesticide biomarkers among farmworkers. This paper presents an overview of PACE3 and provides a descriptive analysis of participant characteristics and one set of pesticide biomarkers, the dialkylphosphate (DAP) urinary metabolites of organophosphorus (OP) pesticides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 17 publications
2
54
1
Order By: Relevance
“…The vast majority of participants reported receiving pesticide safety training (97%), with 80% indicating that the training was provided as recently as the current season. Our study had higher rates of training than a prior study ( N = 287) in which 80% had training in current the season but the other 20% had no training at all (Arcury et al, 2009). …”
Section: Discussioncontrasting
confidence: 67%
“…The vast majority of participants reported receiving pesticide safety training (97%), with 80% indicating that the training was provided as recently as the current season. Our study had higher rates of training than a prior study ( N = 287) in which 80% had training in current the season but the other 20% had no training at all (Arcury et al, 2009). …”
Section: Discussioncontrasting
confidence: 67%
“…High levels of pesticide exposure among migrant and seasonal farmworkers have been documented based on analysis of the dialkylphosphate (DAP) metabolites of OP insecticides 5,6 and of specific metabolites of OP, carbamate, and pyrethroid insecticides. 68 Recent analyses of the OP DAP metabolites indicate that Latino immigrant non-farmworkers also have high levels of detection and concentration for these metabolites, 5,9 indicating that they experience exposure to OP pesticides similar to that of Latino farmworkers.…”
Section: Introductionmentioning
confidence: 99%
“…68 Recent analyses of the OP DAP metabolites indicate that Latino immigrant non-farmworkers also have high levels of detection and concentration for these metabolites, 5,9 indicating that they experience exposure to OP pesticides similar to that of Latino farmworkers. These vulnerable US non-farmworker Latino populations had DAP metabolite concentrations higher than non-agricultural comparison groups in studies conducted outside of the US.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Arcury and colleagues [2009a, 2009b, 2010] examined pesticide urinary metabolites among farmworkers in North Carolina from samples collected in 2007 and reported that farmworkers are commonly exposed to many different pesticides, including organophosphorous (OP), carbamate and pyrethroid insecticides, and several herbicides. They reported that: (1) farmworkers are exposed to different pesticides at different points in the agricultural season; (2) each individual farmworker is exposed to many different pesticides during an agricultural season, and (3) each individual farmworker experiences repeated exposure to specific pesticides several times during the agricultural season.…”
Section: Introductionmentioning
confidence: 99%